In-situ catalytic co-pyrolysis of yellow poplar and high-density polyethylene over mesoporous catalysts. (1st November 2017) - Rezaei, Pouya Sirous; Oh, Daejun; Hong, Yeojin; Kim, Young-Min; Jae, Jungho; Jung, Sang-Chul; Jeon, Jong-Ki; Park, Young-Kwon
Highlights: Meso-MFI catalyzed pyrolysis of yellow poplar gave high aromatic hydrocarbon yield. MFI pore structure, large pore size and strong acidity cause high aromatization. Significant synergy occurred between yellow poplar and HDPE over meso-MFI catalyst. Catalytic pyrolysis efficiency is a strong function of H/Ceff ratio of feedstock. Abstract: Catalytic co-pyrolysis of biomass and hydrogen-rich materials is an effective approach for enhancing the production of bio-based hydrocarbons. In this work, mesoporous solid acid materials, such as hierarchical mesoporous MFI (meso MFI), hierarchical mesoporous Y (meso Y) and Al-SBA-15, were used as the catalysts for the catalytic co-pyrolysis of yellow poplar (YP) and high-density polyethylene (HDPE). Among three catalysts, meso MFI revealed the highest catalytic efficiency for the production of aromatic hydrocarbons from catalytic pyrolysis of YP or HDPE due to its effective pore structure, large channels, and high acidity. Moreover, meso MFI showed the highest synergistic formation of aromatic hydrocarbons during the catalytic co-pyrolysis of YP and HDPE as a result of hydrogen donating effect of HDPE and catalytic interactions between YP- and HDPE-derived pyrolyzates. The amounts of solid residue obtained from the catalytic co-pyrolysis of YP and HDPE over meso MFI were also much lower than their theoretical yields.